2014
DOI: 10.1038/ncomms6413
|View full text |Cite
|
Sign up to set email alerts
|

MNKs act as a regulatory switch for eIF4E1 and eIF4E3 driven mRNA translation in DLBCL

Abstract: The phosphorylation of eIF4E1 at serine 209 by MNK1 or MNK2 has been shown to initiate oncogenic mRNA translation, a process that favours cancer development and maintenance. Here, we interrogate the MNK-eIF4E axis in diffuse large B-cell lymphoma (DLBCL) and show a distinct distribution of MNK1 and MNK2 in germinal centre B-cell (GCB) and activated B-cell (ABC) DLBCL. Despite displaying a differential distribution in GCB and ABC, both MNKs functionally complement each other to sustain cell survival. MNK inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 45 publications
8
87
0
Order By: Relevance
“…S5). Further supporting a role of Mnk2 in the resynthesis of IκBα, we found that treatment of Brd4-deficient BMDMs with the Mnk2 inhibitor cercosporamide (27), which inhibited phosphorylation of eIF4E (Fig. S9A), suppressed LPS-induced IκBα resynthesis accompanied by increased nuclear RelA (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…S5). Further supporting a role of Mnk2 in the resynthesis of IκBα, we found that treatment of Brd4-deficient BMDMs with the Mnk2 inhibitor cercosporamide (27), which inhibited phosphorylation of eIF4E (Fig. S9A), suppressed LPS-induced IκBα resynthesis accompanied by increased nuclear RelA (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Mnk2 and Mnk1 are protein kinases that are directly phosphorylated and activated by ERK or p38 MAP kinases and have been implicated in the regulation of protein synthesis through their phosphorylation of eIF4E at S209 (10,27,28). When we examined the activation of Mnk2 in LPS-treated BMDMs, we found that the cellular levels of Mnk2 decreased with the LPS stimulation in WT BMDMs (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Two recent studies identified increased expression/phosphorylation of specific mRNA translation initiation factors (eIFs), eIF4B and eIF4E, in diffuse large B-cell lymphoma. 8,9 In CLL, stimulation of malignant cells by CD40L-expressing stromal cells increased global mRNA translation and formation of the eIF4F complex, which binds the 59CAP of mRNAs and enhances mRNA translation. 10 Previous comparisons of geneexpression profiling (GEP) and proteomic analysis revealed differences in the transcriptomic and proteomic response after sIgM stimulation of CLL cells, pointing to posttranscriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In adult cardiocytes, overexpression of wild-type MNK1 stimulated translation of mRNA, regardless of the presence of secondary structure in the 5Ј-UTR (49). In diffuse large B-cell lymphoma cells, modulation of MNK1/2 activity differentially affects mRNAs that utilize eIF4E1-versus eIF4E3-driven translation on the basis of a 5Ј-UTR motif (50). In breast carcinoma (MDA-MB-435) cells, ␣6␤4-integrin-dependent activation of MNK stimulates translation of VEGF mRNA, which contains a long, highly structured 5Ј-UTR, but not GAPDH mRNA, which contains a short 5Ј-UTR with little secondary structure (35).…”
mentioning
confidence: 99%